Is cystourethroscopy a crucial preoperative step in severe and complex types of hypospadias? - Oshiba, Ahmed; Kotb, Mostafa (Frontiers in Surgery, 2023)
Background and objectives Proximal hypospadias is considered the most severe subtype of the hypospadias spectrum and represents around one-fifth of the total cases. It is well-evidenced by many studies that the rate of post-operative complications following the repair of this complex subtype is significantly higher when compared to the distal variants. Few reports described the proximal hypospadias from the other perspective which is the pre-operative one. Most pediatric surgeons notice an un-explained incidence of lower urinary tract infection and occasional difficulty of urinary catheterization in those children. This sometimes require the use of additional measures like the use of urethral sounds, filiforms and followers and even catheterization under anesthesia. The aim of the work is to evaluate the role of preoperative cystourethroscopy in detecting associated anomalies in cases of proximal and severe hypospadias. Methods This prospective study was conducted in Pediatric surgery unit at Alexandria Faculty of Medicine from July 2020 to December 2021 and included all children with severe grades of hypospadias. After thorough evaluation, all children underwent cystourethroscopy just before the procedure. Any abnormalities in the urethra, urinary bladder or ureteric openings were recorded if present. Finally, the definitive operation was performed as per-scheduled. Results Fifty-two patients (41 fresh and 11 re-do cases) with a median (range) age at presentation of 5 (1-16) years were enrolled in this study. The intraoperative cystourethroscopy was done in all of the patients. Significant abnormal findings were recorded in 32 patients (61.5%), while the other 20 patients (38.5%) were revealed to be normal. The most common abnormal findings were dilated prostatic utricle opening and hypertrophied verumontanum (in 23 and 16 cases respectively). Conclusion Although most of the associated anomalies with proximal hypospadias are asymptomatic, cystourethroscopy is better used owing to a high incidence of these anomalies. This can facilitate an early diagnosis as well early detection and intervention at the time of repair.